1989
DOI: 10.1111/j.1476-5381.1989.tb11877.x
|View full text |Cite
|
Sign up to set email alerts
|

Vasoactive intestinal polypeptide and non‐adrenergic, non‐cholinergic inhibition in lower oesophageal sphincter of opossum

Abstract: 1 Field stimulation or vasoactive intestinal polypeptide (VIP) relaxed lower oesophageal sphincter (LOS) from North American opossum. Pretreatment with carbachol in Cl-ion-containing or Cl-ionfree Krebs solution or with 10 -M 9-aminoacridine abolished or markedly reduced relaxation due to VIP applied exogenously but not that elicited by field stimulation of non-adrenergic, noncholinergic nerves. 2 Inhibitory junction potentials (7.5 + 1.2 mV, n = 5) could be recorded in LOS strips with the sucrose gap techniqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

1990
1990
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 17 publications
(27 reference statements)
1
11
0
Order By: Relevance
“…These results suggest that the relaxation response is produced by NANC inhibitory nerve excitation. NANC inhibitory nerves have been reported to be present in the guinea-pig caecum (Burnstock et al, 1966), the dog stomach (Ohga et al, 1970), the opossum esophageal sphincter (Daniel et al, 1989), the human uterus (Jones et al, 1997) and the monkey uterus (Kuenzli et al, 1998). The present experiments have demonstrated that functional NANC inhibitory nerves are distributed in the frog esophagus.…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…These results suggest that the relaxation response is produced by NANC inhibitory nerve excitation. NANC inhibitory nerves have been reported to be present in the guinea-pig caecum (Burnstock et al, 1966), the dog stomach (Ohga et al, 1970), the opossum esophageal sphincter (Daniel et al, 1989), the human uterus (Jones et al, 1997) and the monkey uterus (Kuenzli et al, 1998). The present experiments have demonstrated that functional NANC inhibitory nerves are distributed in the frog esophagus.…”
Section: Discussionsupporting
confidence: 50%
“…Nitric oxide (NO) and vasoactive intestinal peptide (VIP) are known as the transmitter substances released from NANC inhibitory nerves (Daniel et al, 1989: Desai et al, 1991: Bayguinov et al, 1999. Further study is required to elucidate the transmitter substances released by NANC excitatory and inhibitory nerves in the smooth muscle of the frog esophagus.…”
Section: Discussionmentioning
confidence: 99%
“…1 Functional studies have suggested that the peptides, vasoactive intestinal polypeptide (VIP), and calcitonin gene related peptide (CGRP) may be candidate NANC inhibitory neurotransmitters in the oesophagus. [2][3][4] Morphological studies in the human oesophagus and in experimental animals show abundant VIP and CGRP in the myenteric plexus, and VIP and CGRP positive fibres in the muscle layers. [5][6][7][8][9][10][11][12] It has now been shown that nitric oxide or a related product of the L-arginine-nitric oxidesynthase pathway may participate in the oesophageal smooth muscle relaxation, latencies of oesophageal contraction, and oesophageal off contraction in the opossum as well as in humans.…”
Section: Introductionmentioning
confidence: 99%
“…Clarification of the underlying mechanisms of the generation of IJP leads to the identification not only of the transmitter(s) but also of the channel(s) involved in these hyperpolarising responses. IJP in LOS are observed in several experimental animals, for example dog (Allescher et al, 1988), opossum (Daniel et al, 1989;Conklin et al, 1993), guineapig (Imaeda et al, 1998;Yuan et al, 1998) and mouse (Ward et al, 1998). In the guinea-pig LOS, nitric oxide (NO) and adenosine triphospahte (ATP) have been proposed as inhibitory neurotransmitters and small conductance Ca 2+ -activated K + (SKCa) channels played an important role in eliciting IJP (Imaeda et al, 1998).…”
Section: Introductionmentioning
confidence: 99%